PERSUASIVE COMMUNICATION STRATEGIES OF THE SEMARANG CITY DEVELOPMENT PLANNING AGENCY (BAPPEDA) IN THE “KITA TANI MUDA” PROGRAM - Yudianisa, Rahma; Luqman, Yanuar (Pena Cendekia Insani, 2026)
Facing a decline in farmers and limited agricultural land, the Semarang City Development Planning Agency (Bappeda Kota Semarang) launched